Methods of State Regulation of Informatization Processes in the Republic of Uzbekistan - N.A.Nugmanov; A.U.Kakhramonova (Researchparks Publishing, 2022)
In the era of information technologies, specialists at various levels of management are faced with the problems of the competent use of tools for regulating the processes of informatization and the issues of the ways of information development of Uzbekistan are being actively discussed. In this article, we have considered on the concept of